2005
DOI: 10.1086/427821
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Near‐Infrared Color Profiles in Nearby Early‐Type Galaxies and the Implied Age and Metallicity Gradients

Abstract: We present results of an age and metallicity gradient analysis inferred from both optical and near-infrared surface photometry. The analysis is based on a sample of 36 nearby early-type galaxies, obtained from the Early Data Release of the Sloan Digital Sky Survey and the Two Micron All Sky Survey. Surface brightness profiles were derived in each band, and used to study the color gradients of the galaxies. Using simple stellar population models with both optical and near infrared colors, we may interpret the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
150
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(177 citation statements)
references
References 64 publications
(89 reference statements)
27
150
0
Order By: Relevance
“…In Section 5.3 we have shown that the median colour gradient in our sample is ∼ 2 times steeper than the measured local (U − R) gradient ∇ U−R from Wu et al (2005).…”
Section: Origin and Evolution Of Colour Gradients With Redshiftmentioning
confidence: 54%
See 3 more Smart Citations
“…In Section 5.3 we have shown that the median colour gradient in our sample is ∼ 2 times steeper than the measured local (U − R) gradient ∇ U−R from Wu et al (2005).…”
Section: Origin and Evolution Of Colour Gradients With Redshiftmentioning
confidence: 54%
“…Tamura & Ohta 2003;Wu et al 2005;Brough et al 2007;Reda et al 2007) as well as in recent simulations (e.g. Hirschmann et al 2015).…”
Section: Methodsmentioning
confidence: 62%
See 2 more Smart Citations
“…Since the SDSS photometrical survey at uand z-bands are much shallower (Fukugita et al 1996) and i-band used a thinned CCD, an instrumental effect known as the "red halo" in the PSF wings are reported to seriously affected the i-band photometric analysis (e.g., Wu et al 2005). We will only derive gand r-band stellar surface brightness distributions by using the standard task ellipse in…”
Section: Radial Surface Brightness Distributionmentioning
confidence: 99%